Analisis Perbandingan RAB dengan Metode SNI 2008 dan AHSP 2022, Studi Kasus : Proyek Ruko di Jl. KR. Rojali, Desa Merah Mata, Lr Belitung, Prajen, Banyuasin I, Banyuasin – Sumatera Selatan - Ridho, M. Effrian; Rachman, Delli Noviarti; Setiawati, Mira (Universitas Muhammadiyah Palembang, 2025)
Before the construction project begins, a financing method is needed to estimate the value of the project. This study uses two RAB methods, namely the SNI 2008 method and the AHSP 2022 method. This study uses the construction of a shophouse on Jl. KR. Rojali, Merah Mata Village, Lr. Belitung, Prajen Banyuasin I, Banyuasin – South Sumatra. The calculation results concluded that using the SNI 2008 method yielded a project construction value of IDR 758,355,000, while the cost estimate using the AHSP 2022 method was IDR 681,878,000. The difference in estimated values between the SNI 2008 method and the AHSP 2022 method shows that the SNI 2008 method is 10% more expensive than the AHSP 2022 method.